Systemic approach in vocational training of human capital as auditor - Rivera León, Félix Armando (2017)
This research is oriented analysis and training in additional studies to the degree specific professional, and other specialties according to your needs, enabling him to have a level of knowledge to intervene in the assessment of the organization under study; Likewise, assess the experience, as ethical / morality, which are acquired through the domain contact day by day in the substantive areas of the organization according to its object, subject matter, allowing contribute to the development of the personal attributes as human capital.